Қарақалпақ фольклорында ана ҳәм бала образы - Жақсылыкова, А; Бекбергенова, М.Д (SCIENCE and SOCIETY, 2016)
The article deals with the educational role of Karakalpak folklore on the basis of the analysis of fairy-tales, proverbs and sayings in which the rela- tions between mother and child, good and bad are expressed. Folklore plays an important role in the education of young generation.
Keywords: folklore; а fairy-tale; sayings; literary interpretation relation between mother and child; image; good and evil; kindness; new think- ing